Kinerja Mengajar Dosen pada Masa Work From Home - Nisa, Lulu Choirun; Hikmaturrokhman, Alfin; Sunardi, Sunardi (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2020)
The Covid-19 pandemic has caused universities to adapt to various changes, especially lecture activities. The purpose of this article is to describe how lecturers carry out the teaching and learning process during a pandemic. The indicators are teaching methods, technology, schedules, evaluation techniques, and constraints. The data collection technique used a survey approach with 216 respondents. The analysis and discussion results show that the teaching method uses online discussions, online assignments, and virtual face-to-face meetings. In terms of technology, the majority of lecturers use the WA Group application, and the rest uses other media. For learning schedule indicators, the majority of lecturers deliver online learning according to the schedule. In evaluation techniques, most lecturers use online tests or quizzes to assess student achievement. The implementation of distance learning has obstacles, namely the achievement and competence of skills and technical barriers, such as signals, devices, and practical delivery skills.